Implementation of the Project-Based Learning (PjBL) Learning Model in Observing Learning Styles and Improving Product Results in Biology Learning at SMAS Sultan Iskandar Muda Medan - Hardiyanti, Putri; Saputra, Andika Dwi; Mardianto, Didi; Simatupang, Halim; Arwita, Widya (Pusdikra-Publishing.com, 2024)
The research was motivated by the problem of student learning styles in group learning and product targets in making project assignments. The aim of this research is to find solutions that can be used to solve problems at SMAS Sultan Iskandar Muda Medan School through Project Based Learning (PjBL). The research method used is quantitative descriptive. The subjects in this research were students of SMAS Sultan Iskandar Muda Medan. This research uses surveys and literature to collect data. Research findings show that the use of the PjBL model can improve students' collaboration abilities in group learning. Students and teachers can utilize available resources to ensure that the tools and materials used by students are accessible. The conclusion of this research is that the PjBL learning model can be an effective solution in overcoming student learning style problems and optimizing product targets in working on project assignments in groups.